The Epidemiological Features of the SARS-CoV-2 Omicron Subvariant BA.5 and Its Evasion of the Neutralizing Activity of Vaccination and Prior Infection - Dandan Tian; Wenjian Nie; Yanhong Sun; Qing Ye (Vaccines, 2022)
From December 2021 to May 2022, the Omicron BA.1 and BA.2 subvariants successively became the most dominant strains in many countries around the world. Subsequently, Omicron subvariants have emerged, and Omicron has been classified into five main lineages, including BA.1, BA.2, BA.3, BA.4, BA.5, and some sublineages (BA.1.1, BA.2.12.1, BA.2.11, BA.2.75, BA.4.6, BA.5.1, and BA.5.2). The recent emergence of several Omicron subvariants has generated new concerns about further escape from immunity induced by prior infection and vaccination and the creation of new COVID-19 waves globally. In particular, BA.5 (first found in southern Africa, February 2022) displays a higher transmissibility than other Omicron subvariants and is replacing the previously circulating BA.1 and BA.2 in several countries.